Novel Oxidative Ugi Reaction for the Synthesis of Highly Active, Visible‐Light, Imide‐Acridinium Organophotocatalysts. Issue 48 (25th July 2018) - Gini, Andrea; Uygur, Mustafa; Rigotti, Thomas; Alemán, José; García Mancheño, Olga
Abstract: A newly designed class of acridinium‐based organophotocatalysts bearing an imide group at the C9‐position is presented. To achieve these unprecedented structures, a synthetic strategy based on a novel straightforward oxidative Ugi‐type reaction at the benzylic position of C9‐unsubstituted acridanes was developed. The introduction of the imide‐unit affords a notable photocatalytic activity enhancement, allowing efficient transformations in different oxidative and reductive visible‐light catalytic reactions. Abstract : Sweet′n′salty : The first, mild, modular, oxidative Ugi reaction on benzylic substrates, such acridanes, allows the development of an unprecedented family of imide‐acridinium visible‐light photocatalysts with boosted reactivities in both oxidative and reductive processes.